If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1a = -5 Solving 1 + -1a = -5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1a = -5 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = -5 + -1 -1a = -5 + -1 Combine like terms: -5 + -1 = -6 -1a = -6 Divide each side by '-1'. a = 6 Simplifying a = 6
| 2w+2=29 | | x+x+60+50+70=180 | | y=-5/2+1.5(7) | | 19-5x=10-8x | | y=-5/2+1/2*7 | | 9x+3=3x+12 | | -1x^2+7x+18=0 | | 100=5x+y+.05z | | 26-4(5x-8)=-2 | | 3(2+6x)-8x(x-5)=4(3x+2) | | 100=5x+y+.05 | | 2500=X+(X*.3) | | -1x^2+7x+72=0 | | 53-(2c+4)=4(c+7)+3 | | 7-2x=3(1-2x) | | -5+z/4= | | 0=-.75x+25 | | 7+k-5-k=k-6 | | 3x-2+5=5x-2x+1 | | 4(5/2+1.5)+3=3(5/2+1.5)+x | | 5-2(2x+3)=x-6 | | 6+18x-8x-40=12+8 | | (8x^2)+20xy+(8y^2)=z | | 5(3f+8)=10 | | 1/2r-1/6r+3=2+1/6r+1 | | 18y+4=10 | | 75=4x-37 | | -10x+12x-18=6 | | 0=28(3)+b | | -1x^2+7x-6=0 | | y^2-13y+36= | | -1x^2-4x-4=0 |